2011
DOI: 10.1523/jneurosci.4430-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

PALS1 Is Essential for Retinal Pigment Epithelium Structure and Neural Retina Stratification

Abstract: The membrane-associated palmitoylated protein 5 (MPP5 or PALS1) is thought to organize intracellular PALS1-CRB-MUPP1 protein scaffolds in the retina that are involved in maintenance of photoreceptor-Müller glia cell adhesion. In humans, the Crumbs homolog 1 (CRB1) gene is mutated in progressive types of autosomal recessive retinitis pigmentosa and Leber congenital amaurosis. However, there is no clear genotype-phenotype correlation for CRB1 mutations, which suggests that other components of the CRB complex may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 43 publications
4
39
0
7
Order By: Relevance
“…Similar defects in the lamination of these cells were also observed in CRB2 null retinas with half of the amount of CRB1 (Crb1 +/2 Crb2Chx10 cKO) (17). These results are in line with (i) previous zebrafish data where Crb2a is required for retinal cell patterning and lamination (30) and (ii) mouse data where the CRB-interacting protein PALS1 affected the correct patterning of photoreceptor cells (31,32).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similar defects in the lamination of these cells were also observed in CRB2 null retinas with half of the amount of CRB1 (Crb1 +/2 Crb2Chx10 cKO) (17). These results are in line with (i) previous zebrafish data where Crb2a is required for retinal cell patterning and lamination (30) and (ii) mouse data where the CRB-interacting protein PALS1 affected the correct patterning of photoreceptor cells (31,32).…”
Section: Discussionsupporting
confidence: 89%
“…Here, we demonstrated that removal of CRB2 from either Müller glial or photoreceptors has similar effect on the apical complexes. This is partially in consonance with observations in PALS1 mutant mice (31,32), and consistent with the epithelial polarity and adhesion defects seen in both the Drosophila Crb mutant and the zebrafish Crb2a (ome) mutant (12,35,36). Short-term depletion of CRB2 in the adult retinas demonstrated that CRB2 is required for maintenance of the retinal structure.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, vertebrate Pals1 stabilizes Crb1 and Crb3 on the plasma membrane of photoreceptor cells and Madin-Darbine canine kidney (MDCK) epithelial cells in culture (Makarova et al, 2003;Park et al, 2011;Roh et al, 2003;van Rossum et al, 2006). Here, we showed that both Pals1 and the AP-2 complex require the same region of mCrb2 for interaction (Fig.…”
Section: Sdt and Ap-2 Antagonize To Control The Surface Level Of Crbmentioning
confidence: 56%
“…Establishing and maintaining proper polarity and OLM integrity are factors crucial for photoreceptor morphogenesis. [29][30][31]33,[45][46][47] In mammals, the classical epithelial polarity PAR6 complex (PAR3/PAR6/aPKCk) localizes to the tight junctions in epithelial cells and to the adherens junctions (AJs) in neuroblasts, and it is a central player in the formation of the junctions and polarization in these cell types. 34,39,41,48,49 A recent study in Drosophila photoreceptors demonstrates that PAR6 and aPKCk form a protein complex that colocalizes to the rhabdomere stalk (equivalent to the IS in mammalian photoreceptors) and that PAR3 localizes to the AJs.…”
Section: Discussionmentioning
confidence: 99%